2011
DOI: 10.1212/wnl.0b013e31823b478c
|View full text |Cite
|
Sign up to set email alerts
|

Severe cutaneous adverse reactions to antiepileptic drugs in Asians

Abstract: CBZ, PHT, and LTG were the major causative AEDs for SCARs. The mortality of PHT-SCARs was higher than CBZ-SCARs due to complicated comorbidity in patients. Nonaromatic AEDs were safe alternatives for patients with aromatic AED-induced SCARs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 31 publications
2
108
1
4
Order By: Relevance
“…One patient on polytherapy (PHT, TPM, and LTG) developed hyperpigmentations. Yang et al reported that LTG, CBZ, and phenobarbital were the major AEDs causing severe forms of CADR in Asians [20].…”
Section: Discussionmentioning
confidence: 99%
“…One patient on polytherapy (PHT, TPM, and LTG) developed hyperpigmentations. Yang et al reported that LTG, CBZ, and phenobarbital were the major AEDs causing severe forms of CADR in Asians [20].…”
Section: Discussionmentioning
confidence: 99%
“…Yang ve ark. 9 antikonvülzan ilaçlardan karbamezepin ve fenitoinin tüm DRESS sendromu vakalarının %43,6'sından sorumlu olduğunu buna karşılık valproik asit ve topiramata bağlı şiddetli kutanöz ilaç reaksiyonuna rastlanmadığını bildirdiler 9 . Valproik asit lamotrijinin metabolizmasını inhibe eder.…”
Section: Discussionunclassified
“…olgu sunumlarında %43,6' sında karbamezepin ve fenitoin sorumlu olduğunu bildirmişlerdir. 8 Benzer şekilde Botelho ve ark. çalışmasında da DRESS sendromuna en sık neden olan ilacın fenitoin olduğu bulunmuştur.…”
Section: Olguunclassified